Optimización del sistema de inventarios de la empresa Monarca Autorepuestos - Bustillos Molina, Juan Carlos (2022)
Keeping an appropriate stock level is the objective that commercial companies must reach in order to achieve an efficient investment, because they only hope to make a profit. For this reason, internal inventory control is seen as a way to reduce the risk of keeping inappropriate stock levels. This research analyzes causes and consequences of main problems that affect the inventory system of Monarca Autorepuestos company, such as reduced space to perform logistics procedures and multiple inconsistencies in the inventory record. To obtain information about logistics procedures of the company, an unstructured interview was applied to its staff, which determined that the main cause of the inventory system problems is the fact that the company staff do not have an efficient control, despite technology in their favor. For this reason, an ABC classification system was proposed for the inventory, aiming that the staff can focus the control efforts on the most important items. Finally, a stock control model was designed for the most demanded items, in which it was determined that the model that best fits on the demand is the Economic Order Quantity model with Safety stock. This model made it possible to answer questions about “when” and “how much” to order, so that stock quantities were optimized, removing the excess to improve warehouse space, without running stockout risk during lead time.